2019
DOI: 10.1177/2333392819826262
|View full text |Cite
|
Sign up to set email alerts
|

Primary Care Provider Continuity Is Associated With Improved Preventive Service Ordering During Brief Visits for Acute Symptoms

Abstract: Background:If a patient presents for an acute care visit and sees their assigned primary care provider (PCP), they may be more likely to receive preventive and other services than a patient not seeing their assigned PCP.Methods:After exclusion of 2 visits with insufficient information, we reviewed 98 consecutive, outpatient internal medicine 15-minute acute care visits comparing patients seeing their assigned PCP with those seeing a non-PCP provider. The primary outcome, preventive service ordering, was measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…The number of contacts is representative of provider continuity and continuity of care. Multiple studies have shown that a higher continuity in family medicine is associated with better outcomes—through improved preventive healthcare27 and more adequate cancer screening28—and lower total healthcare costs 29 30. Our own study has found that patients who see their doctor more frequently had a higher measure of therapeutic alliance, but there was no correlation with the length of time the patient had known their doctor.…”
Section: Discussionmentioning
confidence: 80%
“…The number of contacts is representative of provider continuity and continuity of care. Multiple studies have shown that a higher continuity in family medicine is associated with better outcomes—through improved preventive healthcare27 and more adequate cancer screening28—and lower total healthcare costs 29 30. Our own study has found that patients who see their doctor more frequently had a higher measure of therapeutic alliance, but there was no correlation with the length of time the patient had known their doctor.…”
Section: Discussionmentioning
confidence: 80%
“…Personal continuity implies familiarity and mutual confidence between patient and doctor that can and usually do arise from repeated contacts over time (6). Reported benefits include a better patient-doctor relationship (7,8), better preventive care (9), fewer emergency department visits (10), greater patient and doctor satisfaction (8,11,12), fewer hospital admissions (13), reduced health care costs (14), better medication compliance and prescription (9,(15)(16)(17)(18)(19) and reduced mortality rates (20,21). Adverse effects of personal continuity include frustrated or difficult patient-doctor relationships and delayed diagnosis or referrals (22).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have indicated that having higher continuity is associated with greater treatment adherence in terms of medication use ( 5 7 ). There is even some evidence that continuity with a regular physician is associated with receipt of preventive services ( 8 , 9 ).…”
Section: Introductionmentioning
confidence: 99%